Qualidade de pitaias de polpa branca armazenadas em diferentes temperaturas - Brunini, Maria Amalia [UNESP]; Cardoso, Saulo Strazeio [UNESP] (My University, 2011)
The aim of this paper was to evaluate the effect of storage temperature on the quality of red pitaya of pulp white, produced in Itajobi city, São Paulo state. The pitayas were stored at room temperature, (21-27 °C with 44-63% de UR), at 18 ± 1 °C, with 86-92% RH), 13 ± 1 °C, with 85-90% RH and at 8 ± 1 °C, with 85-95% RH. The quality was monitored during storage time through the parameters: fresh weight loss titleble acidity; soluble solids contents; vitamin C, external appearance, pH and fruit firmness. Through the results obtained may be concluded that the temperature at 8 ± 1 °C it was proportioned the small fresh weight loss; the acidity, soluble solids, pH and fruit firmness were influenced by the storage temperature and storage time, but the temperature at 8 ± 1 °C it was that occasioned the small change theses parameters. In general, it can be concluded that the temperature at 8 ± 1 °C it was the best to maintenance the quality of pitaya fruit.
Quality of stored pitayas fruits white pulp at different temperatures
Keywords: Hylocereus undatus; Post-harvest; Quality; Shelf life; Storage